Application of Non-Linear Fiber Section Model on Spun Piles With and Without Concrete Infill Subjected to Cyclic Loading - Estu Ema Apriliana; Candra Irawan; Priyo Suprobo (Journal of Civil Engineering, 2024)
This numerical analysis study predicts the behavior of spun piles with and withoutconcrete infill under cyclic flexural loading and constant axial load. A fibersection using STKO pre- and post-processor for the OpenSEES program wasemployed. Spun piles were modeled using displacement-based beam-columnelements with distributed plasticity and cyclic loading procedures withdisplacement control. The numerical method proposed for this research wasverified by comparing it to reliable experimental results.